Transformation of Food and Beverage MSMEs in the Digital Era - Triana, Ika; Lestari, Nurul Sukma (Bina Nusantara University, 2025)
Technology challenges for Micro, Small, and Medium Enterprises (MSMEs) are constantly changing. Specifically, this research aims to examine how using digital payments affects the performance of MSME traders in Bekasi's food and beverage industry. The study used quantitative methodology and data processing using Structural Equation Modeling-Partial Least Squares (SEM-PLS) and involved 117 MSME respondents in Bekasi as samples. The results of this study highlight how MSMEs' performance in Bekasi is significantly impacted by their use of digital payment systems. The study shows that MSMEs may maximize the benefits of digital payments if they demonstrate an openness to learning and an acceptance of new technical advancements. Furthermore, as critical components for MSMEs' success in the digital age, the study highlights the vital roles that technology innovation adaptation and training play. MSMEs in the food and beverage industry may improve operational efficiency and competitiveness by identifying and utilizing new technology. This research is limited to certain locations and variables, so further studies are needed with a broader scope and additional variables, such as the role of Pentahelix in developing MSMEs. The implications of this research that can be applied are that adopting technology increases the efficiency, competitiveness, and growth of MSMEs through digitalization and collaboration. Therefore, this research highlights the significance of a proactive strategy for technology integration and ongoing education in enabling MSMEs to prosper in the ever-changing digital ecosystem.